Kepribadian Ideal Konselor dan Konseli dalam Kitab Adab al-Alim wa al-Mutaallim Karya Syekh Hasyim Asy’ari - M. Zidny Nafi' Hasbi; Ruslan Rasid; Muhammad Adnan Firdaus (Islamika Inside: Jurnal Keislaman dan Humaniora, 2022)
Abstract: Counseling as a discipline that focuses on advocating for problem-solving demands to be carried out by individuals who have ideal qualifications so that the counseling carried out can be successful. Several figures have formulated certain ideal criteria for both counselors and counselees. Meanwhile, the book Adab al-Alim wa al-Mutaallim by Sheikh Hasyim Asy'ari has an interesting discussion, namely the classification of the ideal personality of alim (teacher) and mutaallim (student). This concept then makes researchers interested in discussing it from the point of view of counseling science. The purpose of this study is to describe the ideal personal concept of alim and mutaallim and will then be adopted with a counseling approach. The problems to be answered are, 1) what is the ideal personal concept of the counselor in the book of Adab al-Alim wa al-Mutaallim? 2) what is the concept of the counselee's ideal personality in the book of Adab al-Alim wa al-Mutaallim? To answer this problem, the researcher first describes the data related to the ideal personality of the pious and mutaallim and analyzes it (content analysis). From these data, the researcher describes it into categories, continues it in several factors, and then concludes inductively to build an ideal personality theory for counselors and counselees. The results of this study indicate that the ideal personality of the counselor and counselee by adopting the pious and mutaallim personality is divided into two parts, the first is personal and interpersonal personality. The two personal personalities include the entire personality of the counselor and counselee which is internal and not directly related to the opponent. While interpersonal personality is a personality that is directly related to and has an impact on the opponent.